Facial Implants: Controversies and Criticism. A Comprehensive Review of the Current Literature. Issue 4 (October 2018) - Rojas, Yoel A.; Sinnott, Catherine; Colasante, Cesar; Samas, John; Reish, Richard G.
Abstract : Background: Polyethylene (Medpor) and silicone are two of the most popular materials used today for facial skeleton implantation. Previous studies have identified common complications with the use of these implants, but patient follow-up has been short. This review of the literature examines complications and patient follow-up in cases using Medpor and silicone implants for reconstructive and aesthetic operations of the mid and lower face over the past 20 years. Methods: A literature search was conducted through the PubMed database. Keywords used were as follows: ("mandible implants" or "malar implants" or "chin implants") AND ("reconstruction" or "augmentation") AND ("Medpor" or "silicone"). Results: There were nine studies with 626 patients in the Medpor group and five studies with 365 patients in the silicone group. The silicone group had a higher incidence of infections and displacements. The Medpor group showed a higher incidence of prominence problems. Exposure/extrusion rates were low for both implant types. Chin and mandibular implants were the safest, whereas malar implants had a high incidence of prominence problems. The average follow-up for Medpor was 36.6 months and 24 months for silicone. There were wide ranges of follow-up times, from 2 weeks up to 15 years. A limited number of articles included an averaged time within their ranges. Reported follow-up times were not linked to specific complications. Conclusions: Medpor implantation is more common than silicone. Complication rates are low with the use of both materials. Patient follow-up is deficient and has not improved in the past 20 years, raising questions on the reliability of complication rates.